Dysconnectivity of Multiple Resting-State Networks Associated With Higher-Order Functions in Sensorineural Hearing Loss - Luan, Ying; Wang, Congxiao; Jiao, Yun; Tang, Tianyu; Zhang, Jian; Teng, Gao-Jun (Frontiers in Neuroscience, 2019)
Objects: Sensorineural hearing loss (SNHL) involves wide-ranging functional reorganization, and is associated with accumulating risk of cognitive and emotional dysfunction. The coordination of multiple functional networks supports normal brain functions. Here, we aimed to evaluate the functional connectivity (FC) patterns involving multiple resting-state networks (RSNs), and the correlations between the functional remodeling of RSNs and the potential cognitive or emotional impairments in SNHL. Methods: Thirty long-term bilateral SNHL patients and thirty-nine well-matched healthy controls were recruited for assessment of resting-state functional magnetic resonance imaging (rs-fMRI) and neuropsychological tests. Results: Using independent component analysis (ICA), 11 RSNs were identified. Relative to the healthy controls, patients with SNHL presented apparent abnormalities of intra-network FC involving right frontoparietal network (rFPN), posterior temporal network (pTMN) and sensory motor network (SMN). Disrupted between-network FC was also revealed in the SNHL patients across both higher-order cognitive control networks and multiple sensory networks. Eight of the eleven RSNs showed altered functional synchronization using a seed network to whole brain FC method, particularly in the ventromedial prefrontal cortex (vmPFC). In addition, these functional abnormalities were correlated with cognition- and emotion-related performances. Interpretations: These findings supported our hypotheses that long-term SNHL involves notable dysconnectivity of multiple RSNs. Our study provides important insights into the pathophysiological mechanisms of SNHL, and sheds lights on the neural substrates underlying the possible cognitive and emotional dysfunctions following SNHL.